Application of the Drowning Index to Opioid & Multidrug Intoxication Deaths: A Retrospective Analysis. Issue 1 (March 2019) - Ellis, Lindsey T; Opsahl, Madeleine; Duff, Deiter J.; Stacy, Carl C.
Introduction: Drowning deaths present a challenge for forensic pathologists, because the autopsy findings may occur in many nondrowning scenarios. Previous studies have attempted to identify patterns in organ weights that may be specific for drowning. The drowning index (DI) has been defined as the weight ratio of the lungs and pleural effusion fluid to the spleen. Studies have suggested DI may be useful in confirming drowning as the cause of death. No studies have yet compared autopsy findings in drownings to those in drug-related deaths, in spite of their qualitative similarities. Materials and Methods: We compared the lung and pleural effusion weight, spleen weight, and DI from 536 autopsies ruled drowning, opioid, or multidrug intoxication, or hanging in Columbia, Missouri, from 2011 to 2016. Results: Opioid overdoses result in heavier lungs and spleens than drownings, multidrug overdoses, or hangings. There is no DI value at which a death can be definitively ascribed to drowning. The median DI was significantly higher in drownings than in opioid intoxications, multidrug intoxications, or hangings ( P < .0001; P = .001; P = .005). However, very few drowning cases (13.33%) had a DI >14.1. Additionally, many opioid and multidrug overdoses had a DI >14.1. The highest calculated DI value (DI = 33) was associated with multidrug intoxication. Conclusion: In our opinion, the DI has little, if any, utility in distinguishing between drowning and drug-related deaths.